Effect Of Electroplating Industrial Effluent Chromium On Bimodal Respiratory Rhythm Of The Air-Breathing Cat Fish Mystus cavasius (Ham) - Palanisamy, P (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTEffect of sublethal (0.25%) concentration of electroplating Industrial effluent chromium on bimodal respiratory rhythm of Mystus cavasius (Ham) was studied. Result revealed that at sublethal concentration the respiratory rhythm was significantly disrupted. The significance of the results is discussed from a chronotoxicological point of view.